Manipulation of the Tubulin Code Alters Directional Cell Migration and Ciliogenesis - Müller, Manuel; Gorek, Lena; Kamm, Natalia; Jacob, Ralf (Frontiers in Cell and Developmental Biology, 2022)
Conjunction of epithelial cells into monolayer sheets implies the ability to migrate and to undergo apicobasal polarization. Both processes comprise reorganization of cytoskeletal elements and rearrangements of structural protein interactions. We modulated expression of tubulin tyrosin ligase (TTL), the enzyme that adds tyrosine to the carboxy terminus of detyrosinated α-tubulin, to study the role of tubulin detyrosination/-tyrosination in the orientation of cell motility and in epithelial morphogenesis. Oriented cell migration and the organization of focal adhesions significantly lose directionality with diminishing amounts of microtubules enriched in detyrosinated tubulin. On the other hand, increasing quantities of detyrosinated tubulin results in faster plus end elongation of microtubules in migrating and in polarized epithelial cells. These plus ends are decorated by the plus end binding protein 1 (EB1), which mediates interaction between microtubules enriched in detyrosinated tubulin and the integrin-ILK complex at focal adhesions. EB1 accumulates at the apical cell pole at the base of the primary cilium following apicobasal polarization. Polarized cells almost devoid of detyrosinated tubulin form stunted primary cilia and multiluminal cysts in 3D-matrices. We conclude that the balance between detyrosinated and tyrosinated tubulin alters microtubule dynamics, affects the orientation of focal adhesions and determines the organization of primary cilia on epithelial cells.